A Learning Process Evaluation Model for the Integrated Islamic Elementary School - Retno Wahyuningsih; Khuriyah khuriyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
The study was to: 1) generate the appropriate evaluation instrument so that the instrument might be implemented in evaluating the Integrated Islamic Elementary School (SDIT, Sekolah Dasar Islam Terpadu) learning process; 2) identify the effectiveness of the developed evaluation instrument; and 3) identify the description and the criteria in the results of evaluation conducted in the Integrated Islamic Elementary School. The study was categorized as an evaluation research that applied the CIPP evaluation model (the aspects that had been selected were the input and the process), namely the one that referred to the steps in the research and development efforts in order to develop the instrument for evaluating the learning process in the Integrated Islamic Elementary School. The conclusions of the study, then, are as follows: 1) the study has generated the Integrated Islamic Elementary School Learning Process Evaluation Model (P3) and the P3 Model that has been developed refers to the theory of Borg Gall that consists of 9 stages; 2) the P3 Model has a â€œVery Goodâ€ effectiveness based on the reviewer assessment and has met the standards of a tool that might be applied for evaluating the learning process in the Integrated Islamic Elementary School; and 3) the criteria in the P3 Model might provide a factual and overall description regarding the learning process in the Integrated Islamic Elementary School.